2013
DOI: 10.4103/0019-5154.108086
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral multi-segmental leiomyomas: A report of rare case

Abstract: A 30-year-old female presented to us with multiple tender erythematous papules and nodules. These lesions showed multi-segmental distribution along 5th cervical, 6th dorsal, and 1st sacral segments of right half of the body. Histopathological examination confirmed the clinical diagnosis of leiomyoma. Patient was started on nifedipine 10 mg thrice-daily with significant symptomatic improvement in 3 months. Though segmental distribution of leiomyoma is common, unilateral multi-segmental distribution has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…[ 6 7 ] Though the precise molecular mechanisms that lead to the development of multiple cutaneous leiomyomas are unknown, recent studies have demonstrated the mutation of a gene encoding fumarate hydratase, on chromosome 1q42.3-43 that predispose individuals to MCUL and HLRCC. [ 3 8 9 ] There was no family history of uterine or cutaneous leiomyoma in our patient, neither was there any finding suggestive of renal neoplasm affecting the patient himself. The clinical profile of our patient was suggestive of non-familial type 2 segmental leiomyoma.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…[ 6 7 ] Though the precise molecular mechanisms that lead to the development of multiple cutaneous leiomyomas are unknown, recent studies have demonstrated the mutation of a gene encoding fumarate hydratase, on chromosome 1q42.3-43 that predispose individuals to MCUL and HLRCC. [ 3 8 9 ] There was no family history of uterine or cutaneous leiomyoma in our patient, neither was there any finding suggestive of renal neoplasm affecting the patient himself. The clinical profile of our patient was suggestive of non-familial type 2 segmental leiomyoma.…”
Section: Discussionmentioning
confidence: 78%
“…Multiple piloleiomyomas may be inherited in an autosomal-dominant fashion and may be associated with uterine leiomyomas and aggressive renal carcinoma, also known as multiple cutaneous and uterine leiomyomatosis (MCUL) or Reed's syndrome and hereditary leiomyomatosis and renal cell carcinoma (HLRCC), respectively. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8 A rare case of unilateral multi-segmental cutaneous leiomyoma of type I has also been reported. 9 Pathogenesis of pain is hypothesized to be due to local pressure exerted by the tumor on the cutaneous nerves or due to local ischemia caused by muscle contraction. 3,4 The differential diagnoses include dermatofibroma, neurofibroma, schwannoma, angiolipoma, eccrine spiradenoma, granular cell tumors and glomus tumor.…”
Section: Discussionmentioning
confidence: 99%
“…CL account for 75% of extrauterine leiomyomas [1]. According to their site of origin, leiomyomas may be classified into piloleiomyomas, angioleiomyomas, and genital leiomyomas [2]. Piloleiomyomas are derived from the arrector pili muscle of the hair follicles, whereas angioleiomyomas are derived from the vascular smooth muscle.…”
Section: Introductionmentioning
confidence: 99%